USE OF THE DANA DIGITAL WALLET APPLICATION AND ITS IMPACT ON PUBLIC LIFE - Susanti Nadintia; M. Rifani; Muhammad Fauzan (Indragiri Research Center (ingreat), 2025)
The development of digital technology is driving changes in people's payment systems, one of which is through the use of digital wallets. This study aims to determine the use of the DANA digital wallet application and its impact on society. This study used a qualitative approach with data collection methods through interviews and observations of DANA application users. The results show that the use of the DANA application provides convenience in conducting financial transactions, increases time efficiency, and fosters public trust through the available security system. In addition, promo and cashback features influence people's consumption behavior, although they have the potential to encourage consumptive attitudes if not used wisely. The DANA digital wallet application also plays a role in increasing financial inclusion by providing wider access to financial services for the public. Thus, the use of the DANA application not only functions as a digital payment tool, but also has a social and economic impact on people's lives.